Pengaruh Digital Marketing dan Kepercayaan Konsumen Terhadap Kepuasan Pembelian di TikTok Shop - Naim, Muhammad; Eikman, Alfian; Nabila, Nur (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This study aims to analyze the influence of digital marketing and consumer confidence on purchase satisfaction on the TikTok Shop platform. TikTok Shop is one of the short video-based social media that has now developed into a means of electronic commerce that is of interest to the public, especially the younger generation. The research method used is quantitative with causal approach (explanatory). The Data was collected through the distribution of questionnaires to 50 respondents who had made purchases on TikTok Shop. The results showed that partially digital marketing does not have a positive effect on purchase satisfaction and for consumer confidence variables proved to have a positive effect on purchase satisfaction.But simultaneously, the results of the third hypothesis show that Digital marketing and consumer confidence contribute positively to increasing purchase satisfaction in TikTok Shop. These findings indicate that ineffective digital marketing strategies and efforts to build customer trust are important factors in creating a satisfying shopping experience on social media-based e-commerce platforms such as TikTok Shop